Azerbaijan : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
In the area of the country's financial accountability framework, Azerbaijan has already received and continues to receive a considerable amount of analysis, advice, and assistance, particularly in the areas of public financial management from the International Monetary Fund, the World Bank, USAID, and lately, the European Union.. This CFAA summarizes the analysis performed to-date as well as any associated advice and development assistance and also identifies areas hitherto un-addressed and provides a framework to address issues arising. This report comprises a matrix summarizing ongoing financial management initiatives and CFAA recommendations. In respect of private sector enterprise accounting, the CFAA recommends re-establishing the Council of Accountants with responsibility for preparing and determining accounting standards; developing a plan to harmonize the various sources of accounting guidance; relying more on auditor's conclusions to determine compliance with relevant accounting standards; and developing training and capacity building programs. Regarding private sector enterprise auditing, the CFAA recommends having the Civil Code define the entities required to have an audit; amending the laws on auditing; and adopting international standards on auditing. To strengthen the banking sector, the CFAA recommends coordination to develop banking accounting standards; and setting professional qualifications for auditors. To reinforce financial accountability aspects of the country's corporate governance framework, the laws should clarify the roles and resources available to an entity's financial auditing commission. The report also recommends establishing an oversight group and reviewing audit firms to confirm their acceptability.